The Influence of Independent Learning on Entrepreneurial Attitudes Through Business Motivation as an Intervening Variable (Case Study on Open University Students at UPBJJ-UT Majene) - Nurdiyah Nurdiyah; Anfas Anfas; Fajar Rakasiwi Syamsuddin; Syahrinullah Syahrinullah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research aimed to determine the influence of independent learning on entrepreneurial attitudes through business motivation as an intervening variable on Open University students at UPBJJ-UT Majene. The sampling technique used was the purposive sampling method. There were 43 students. While the data analysis used the regression analysis method. The results showed that: (1) the independent learning variable obtained t values of 4,265 with a sig value of 0.000. Therefore, it is concluded that there is a positive and significant influence between learning independence variable and entrepreneurial attitudes; (2) the independent learning variable obtained t values of 6,743 with a sig value of 0.000. Therefore, it is concluded that there is a positive and significant influence between independent learning variable and business motivation; (3) the business motivation variable obtained t value of 8,838 with a sig value of 0.000. Therefore, it is concluded that there is a positive and significant influence between business motivation variable and entrepreneurial attitudes; (4) hypothesis testing path analysis model in equation-2 The regression coefficient value is 0.725 and significant at 0.000, which means the independent learning variable has a positive and significant effect on business motivation. The regression coefficient value of 0.725 is the path value (P2)